Upaya Orangtua Dalam Membentuk Perilaku Positif Anak Usia Dini di Era Digital - Dinu Rijkiah; Muthia Sari; Devi Ayu Kurniawati (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The digital era presents new challenges in parenting early childhood. Children are easily exposed to digital content that is not always appropriate, making the role of parents crucial in shaping positive behavior. This study aims to describe parental efforts in fostering positive behavior in early childhood during the digital era. The research employed a qualitative approach with a descriptive method. The subjects were parents of students at RA Assyukron. Data were collected through interviews, observation, and documentation, and analyzed using Miles and Huberman’s interactive model. The results show that parents engage in active supervision, monitor media content, model good behavior, and instill moral values from an early age. The main challenges encountered include the uncontrollable influence of digital media and inconsistency in parenting within extended families. In conclusion, parenting in the digital era requires adaptive and reflective strategies to ensure that children grow up with strong and consistent positive behavior